…Christianity’s belifes in the Hujaz before advent Islam … - Hashem, Zeena Qassem (Al-Adab Journal, 2015)
Christian thoughts in Hijaz and released Islam? And going on the third chapter of Christianity in Najd and al-Yamamah and section on Mbgesin first looking Christianity in Najd between tribes Collapse Kinda and kings built eat bitterness Christians and king contagious bin distressed Christian first converted to Christianity and helped the spread between the sons of Kinda and Christianity in the Al-Yamamah between the tribe sons Hanifa mentioned details about this tribe and Christian until the beginning of the emergence of Islam and the defection of some of its members were Musaylimah liar. The second section came in Christianity in the eastern boundary of the Arabian Peninsula dealt with Christianity between the tribe Tamim and Bakr bin Wael and converting to Christianity in the fourth century AD impact Akea and Christianity between Abdul Qais in Bahrain, Christianity in the Hijaz about Christianity in the cities of revelation anywhere descent of the Holy Quran and the beginning of the Islamic Dawa was the era of the Prophet The second came from the Nestorian Christianity in Yathrib, as Triangle station of trading caravans, which followed a long road of confusion and then to the Levant through the market Nawfal and Osman bin Huwayrith Lama Taif Vtnolna where personal Addas. .Jandal, these long distance made of Yathrib, a place to rest and also for Christian Mecca